Assessing The Role of Halal Certification in Shaping Micro, Small, and Medium Enterprises’ Perceptions and Income - Ramadhani, Rega; Widiawati; Wira Dana Kusuma, Suteja; Zaky, Muhammad (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
Halal certification has become increasingly important among Micro, Small, and Medium Enterprises (MSMEs), especially in the food and beverage sector, following the implementation of Indonesia’s Law No. 33 of 2014 concerning Halal Product Assurance. This certification serves both as a regulatory requirement and a means to gain consumer trust, particularly from the Muslim majority. This study aims to explore the impact of halal certification on business actors’ perceptions and income levels within the traditional market area of Pasar Tumpah, Komplek Bumi Harapan, Bandung Regency. A descriptive qualitative method was used. Primary data were collected through direct observation and semi-structured interviews with nine culinary business owners. Six of whom were certified halal and three were not. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that certified business owners generally perceive halal certification positively, recognizing its benefits in improving consumer trust and business image. However, only two of the six certified businesses reported a noticeable increase in income. The remaining four did not experience significant financial changes. Uncertified respondents acknowledged the value of halal certification but cited cost and process complexity as primary barriers. Halal certification contributes positively to the perception of MSMEs in traditional markets, though its direct impact on income may vary. Support mechanisms may be needed to assist small businesses in obtaining certification.